Internet and Multimedia Training For Young Generations - Iwan Kurniawan; Yudhi Chandra (Jurnal Pengabdian Barelang, 2019)
businesses, but now it can be said that the internet has become one of the mandatory things for various groups, especially the majority of young people. Technological advances are the answer to the progress of globalization that is increasingly enveloping the world. A progress that will certainly have an impact on the civilization of the student's life. The large number of students who also act as users of information and communication technology, proves that their lives are never separated from the role of information technology. The ease of accessing the internet, such as the many scattered internet cafes, schools that began to provide facilities and provide lessons on the internet. But this is not balanced with knowledge about the use and use of the internet that is good for some groups. There is a possibility that there is an abuse of the internet for things that are harmful. The target of the implementation of this service activity is the youth group of kelurahan Kelapa Dua, Tangerang. The target of this training is to get an overview of the use of information technology in this case the internet as a form of activity and work tools in various fields, acquiring skills regarding internet use that can be used as information and entertainment media, and finally, make young people more creative and innovative and applying knowledge that is owned to the community. The output of this activity is to increase knowledge and skills for the younger generation in using and using the internet well. Also the younger generation is able to optimize the use of the internet in existing resource development activities.